2021
DOI: 10.1155/2021/8323189
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Observation of Effects of Prepregnancy Body Mass Index and Weight Gain during Pregnancy on Neonatal Weight and Delivery Outcome

Abstract: Objective. The increase of BMI before pregnancy and during pregnancy will lead to hypertensive disorder in pregnancy (HDP) and abnormal glycolipid metabolism, as well as increase the risk of neonatal weight abnormalities and adverse pregnancy outcome. This study retrospectively analyzed the clinical data of 358 women who were admitted to the obstetrics department of our hospital from January 2018 to July 2019. And the relationship between prepregnancy BMI, BMI increase during pregnancy and delivery methods, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Saturated fat (E %) 2,3 MUFA (E %) 2,3 PUFA (E %) Protein from dairy (E %) 2,3 Protein from seafood (E %) 5,6 25.1 ± 4. Total sugar (E %) 2,3 Fiber (g/100 kcal/d) 3,7 Glycemic index 8,9 42.7 ± 6.5 %, percentage of total energy consumption. 2 Presented as percent of total energy intake from an average of two 24-hr recalls.…”
Section: Dietary Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Saturated fat (E %) 2,3 MUFA (E %) 2,3 PUFA (E %) Protein from dairy (E %) 2,3 Protein from seafood (E %) 5,6 25.1 ± 4. Total sugar (E %) 2,3 Fiber (g/100 kcal/d) 3,7 Glycemic index 8,9 42.7 ± 6.5 %, percentage of total energy consumption. 2 Presented as percent of total energy intake from an average of two 24-hr recalls.…”
Section: Dietary Intakementioning
confidence: 99%
“…This concern is particularly relevant for women with overweight or obesity [defined as a body mass index (BMI) ≥25 kg/m 2 or ≥ 30 kg/ m 2 , respectively], because excess body weight and body fat during pregnancy are associated with many health risks, including increased risk of cesarean section, premature delivery, excess birthweight, abnormal glucose and lipid metabolism, hypertensive disorders, postpartum hemorrhage and neonatal asphyxia (6)(7)(8). Hypertensive disorders, in particular, are associated with an increased risk of pulmonary edema, placental abruption, small-for-gestational age, and even perinatal death (9).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal overweight and obesity can affect the gestational process, as well as delivery and the postpartum health of both mothers and their infants. In addition to pre-pregnancy body weight, gestational weight gain (GWG) also plays an important role in maternal and infant health outcomes ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%